Monoclonal antibodies to lipoarabinomannan/arabinomannan – characteristics and implications for tuberculosis research and diagnostics. Issue 1 (January 2023) - Corrigan, Devin T.; Ishida, Elise; Chatterjee, Delphi; Lowary, Todd L.; Achkar, Jacqueline M.
Abstract : Antibodies to the mycobacterial surface lipoglycan lipoarabinomannan (LAM) and its related capsular polysaccharide arabinomannan (AM) are increasingly important for investigations focused on both understanding mechanisms of protection against Mycobacterium tuberculosis ( Mtb ) and developing next-generation point-of-care tuberculosis (TB) diagnostics. We provide here an overview of the growing pipeline of monoclonal antibodies (mAbs) to LAM/AM. Old and new methodologies for their generation are reviewed and we outline and discuss their glycan epitope specificity and other features with implications for the TB field. Highlights: The related surface glycans lipoarabinomannan (LAM) and arabinomannan (AM) play important roles in interactions between Mycobacterium tuberculosis ( Mtb ) and other mycobacteria and the host. These conformationally flexible glycans are shed in vitro and in vivo . The pipeline of monoclonal antibodies (mAbs) to LAM/AM has grown as antibodies to LAM and AM are important for studies both to understand mechanisms of protection against Mtb and to develop next-generation simple point-of-care tuberculosis diagnostics based on LAM detection in body fluids. The synthesis of oligosaccharides corresponding to structurally defined LAM/AM motifs, and their display in an array format, has enabled convenient characterization of anti-LAM/AM antibody reactivity to glycan epitopes. To date, the epitope specificity of 21 mAbs to LAM/AM has been determined. These data enhance our understanding of LAM/AM motif recognition and its relevance for antibody functions and diagnostic LAM detection.